ANALYSIS OF DOMAIN SPECIFICITY OF THE PROTECTIVE CHIMERIC ANTIBODY ch14D5a AGAINST GLYCOPROTEIN E OF TICK-BORNE ENCEPHALITIS VIRUS - I. K. Baykov; L. A. Emelyanova; L. M. Sokolova; E. M. Karelina; A. L. Matveev; I. V. Babkin; Ya. А. Khlusevich; V. F. Podgornyy; N. V. Tikunova (Вавиловский журнал генетики и селекции)
A drug for the prevention and therapy of tick-borne encephalitis virus is being developed on the basis of the protective chimeric antibody ch14D5a. At the same time, the epitope recognized by this antibody on the surface of glycoprotein E has not been localized yet. The aim of this work was to identify the domain of glycoprotein E, to which the protective antibody ch14D5a binds. As a result, four recombinant variants of glycoprotein E were generated using the bacterial expression system: (1) the rE protein containing the domains D1, D2, and D3 of glycoprotein E; (2) the rED1+2 protein containing domains D1 and D2; (3) the rED3_301 protein, which is domain D3 of glycoprotein E, and (4) the rED3_294 protein comprising domain D3 and a hinge region connecting domains D1 and D3. The rED3_294 and rED3_301 proteins were obtained in soluble monomeric form. The rE and rED1+2 proteins were extracted from the inclusion bodies of Escherichia coli. Using Western blot analysis and surface plasmon resonance analysis, it was demonstrated that the protective chimeric antibody ch14D5a and its Fab fragment bound specifically to domain D3 of glycoprotein E. Since the antibodies recognizing epitopes on the surface of domain D3 do not tend to cause antibody-dependent enhancement of the infection as compared to antibodies directed to domains D1 and D2, the data obtained confirm the promise of using the antibody ch14D5a in the development of a therapeutic preparation against the tick-borne encephalitis virus.